Management of fracture risk in Parkinson's: A revised algorithm and focused review of treatments. (July 2019) - Henderson, Emily J.; Lyell, Veronica; Bhimjiyani, Arti; Amin, Jigisha; Kobylecki, Christopher; Gregson, Celia L.
Abstract: Introduction: Falls and fractures are a cause of substantial morbidity in Parkinson's. Despite an excess risk of both falls and osteoporosis, people with Parkinson's perceive that they are less likely to fracture than their peers, despite actually being at higher fracture risk. Recognising this increased risk, in 2014 we published an algorithm to guide management of fracture risk in this high-risk population. Recently, the National Osteoporosis Guideline Group (NOGG) published new guidance revising the 10 year fracture probability intervention thresholds for those over 70 years old to 20.3% for major osteoporotic fracture and 5.4% for hip fracture. Methods: In light of the new guidance, we have reappraised the use of two fracture prediction tools, Qfracture and FRAX, and have updated the algorithm to guide the management of bone health and fracture risk in people with Parkinson's. Results: We outline the treatment options available with particular consideration given to Parkinson specific factors that influence treatment choices. Conclusion: This guidance is relevant to all healthcare specialist managing Parkinson's including neurologists, geriatricians and primary care practitioners. Highlights: People with PD have a substantially increased risk of fragility fracture, especially of the hip. Management of bone health should be provided routinely to all patients with movement disorders. FRAX and NOGG can be adapted to better suit the assessment of people with Parkinson's. The new BONE-PARK algorithm guides assessment and management of fracture risk in Parkinson's. Bisphosphonates remain first line treatment, but specific consideration should be given to parenteral therapy.